OpenStudy (anonymous):

HELP, PLEASE! FAN and MEDAL [01.01] Given the equation 5x − 4 = –2(3x + 2), solve for the variable. Explain each step and justify your process. Megan solved a similar equation below. Is Megan's solution correct? Explain why or why not. 3(2x − 4) = 5x − 1 6x − 12 = 5x − 1 11x − 12 = –1 11x = 11 x = 11

2 years ago
OpenStudy (nkhanfar):

its correct because when you change the values from one side to the other they change signs for example if its positive it will change into negative and if its negative it will change into positive dont take my word for it

2 years ago
Similar Questions: